(untitled) (Journal of Academic Research, 2021)
Disputes in labor cases are one of the most important issues that arise between the worker and the employer, which drives them to search for a way to resolve these disputes as an alternative to the judiciary, and among the most important of these methods: the arbitration path, which is an exceptional way for the parties to the contract to settle the dispute between them, given the arbitration feature, which is shortening time and lower costs And the speed of settlement of disputes. For this reason, the nature of the research necessitated the answer to some of the following problems, namely: To what extent is it permissible to resort to arbitration as an alternative to the judiciary in adjudicating labor disputes? To what extent can arbitration resolve these disputes arising from the employment contract? To answer these problems; It is necessary to divide this research into three demands. The first condition will be defined as the essence of arbitration in labor matters, while the second requirement will be dealt with in the arbitration agreement, and in the third and last requirement, the suitability of resolving labor disputes through the arbitration system will be clarified.